Legumes flour: a review of the nutritional properties, physiological functions and application in extruded rice products. (4th August 2022) - Guan, Chunmin; Long, Xinkang; Long, Zhao; Lin, Qinlu; Liu, Chun
Summary: In recent years, legumes have become increasingly popular because of their high nutritional value and health benefits. Moreover, most legumes have a low glycaemic index (GI) and are often considered in dietary interventions for diabetes. Extruded rice products (ERPs) are trendy in major rice‐producing areas, including staple foods (such as rice noodles) and snack foods (such as rice cake). However, ERPs have a higher GI and a relatively simple nutritional composition. Therefore, adding whole legumes flour or its components to ERPs is a significant issue, which can reduce ERPs' GI and improve these products' nutritional value. This paper reviewed the nutritional properties and physiological functions of legumes flour or its components. In addition, the factors (starch and extrusion processing) affecting the quality and GI of ERPs were summarised. Besides, this paper reviewed after adding whole legumes flour or its components to ERPs, the products' appearance and quality are better and its nutritional properties are also better, especially with regard to type 2 diabetes mellitus (T2DM). Moreover, this review also summarised three‐dimensional (3D) printing technology in ERPs could improve the products' quality and nutritional value. Finally, directions that will be the focus of 3D printing and legumes were highlighted. Abstract : Health benefits of extruded rice products fortified with legumes flour.